UMP, KUAS tie-up to enhance mould & die manufacturing - UMP, PNC
To further develop the mould and die manufacturing industry in Malaysia, Universiti Malaysia Pahang (UMP) has entered into an academic and research collaboration with Taiwan’s National Kaohsiung University of Applied Sciences (KUAS), with the signing of a Memorandum of Understanding (MoU) at the Banquet Hall of UMP’s Chancellery on August 3, 2010.